The illustrated encyclopedia of the pyramids, temples and tombs of ancient Egypt : discover the fascinating and mysterious world of the pharaohs with insightful text and more than 400 stunning colour photographs - 382660 Oakes, Lorna (London : Southwater, 2006)
32